Emotional Intelligence And Participation In Campus Organizations - Wahyu Budi Santoso; Ririn Dewanti Dian Samudra Iriani (Universitas Muhammadiyah Sidoarjo, 2013)
Emotional intelligence is very influential to achieving success even for someone everyday life. However, there is a difference between the students emotional intelligence whose join in organization with whose do not join in the organization. The purpose of this study was to find out the difference between student emotional intelligence in terms of participation in campus organizations for UMSIDA student. This study used a quantitative approach. The variables of this study were students whose joined in campus organization and whose not as an independent variable (X) and student emotional intelligence as the dependent variable (Y). Purposive sampling was implemented as the sampling technique for 125 students whose joined in the organization and 125 students whose did not join in campus organization as predetermined character. t-test analysis used to analyze difference between data which calculated by SPSS-17 For Windows. The result shown that t = - 5,584 and p<0,05 (0,000<0,05), this means that there are differences between student emotional intelligence who join in campus organization with whose not.